Information Quality in Web-Based eCatalogue - Alsarhan, Ali Bassil (2009)
Catalogues are important business strategy as they can provide customers with product descriptions and assist who have buying interest to not go through the floor areas and shelves, browsing aimlessly, trying to locate items that are of interest. Printed catalogue are cumbersome to use, require large storage areas, become dated soon after publication, and make search and comparison activities very difficult.The situation is further worsen when the quality of information provided is not regularly updated and is below customers’ expectations. eCatalogue has the potential to offer assistance to customer, and improve information quality.Therefore, an eCatalouge was developed in this study where 30 potential customers tried the proposed eCatalogue for a certain period. Nine information quality dimensions, which are Accuracy, Precision, Currency, Timeliness, Reliability,Completeness, Conciseness, Format, and Relevance, were used to measure the eCatalouge. Based on a three point scale (where 1= disagree and 3= agree),respondents agree that the information in the eCatalouge are somewhat current(mean =2.27), precise (2.20), accurate (2.17), reliable (2.17), and concise(2.17). However, they are not sure about the timely (2.00) and relevant (2.07) dimensions.Also they agree to some extent, the eCatalogue format is satisfying (2.20). Overall mean of quality measure is (2.15), which is indicates that the quality of information in the developed eCatalogue should be improved.